Chinese students study the vocabulary of scientific style of the russian language - Wang, Yameng (Universidade Estadual Paulista, 2021)
This paper investigates the teaching of scientific style of speech to Chinese students. From the point of view of teaching scientific style of speech, the issue of teaching Chinese is currently controversial. This study uses the following methods: research of scientific literature and various statistical data; study of curricula designed for foreign students; analysis of available information about universities that accept Chinese students. It is necessary to say that today's teaching practice brings forward new problems that are controversial. It should be noted that the formation of foreign language communication among students requires the development of a unified system of teaching, which would be focused on the practical activities of future professionals. Interdisciplinary interaction of teachers and closely related general and special discipline should be at the core of foreign language teaching.